What makes Critical Religion critical? A response to Russell McCutcheon - Goldstein, Warren S. (Critical research on religion, 2020)
This is a response to Russell McCutcheon's (2018) book chapter titled "On Concepts and Entities: Varieties of Critical Scholarship" in which he criticizes the value-driven approached advocated in previous editorials of Critical Research on Religion. This response points out that critical religion (the approach of McCutcheon and others) is also value-driven and not non-normative as he claims, but that this is what makes it critical.